Supporting the Truth and Its Contemporary Applications: In Light of Surah al-Asr - Ahmad, Muhammad Shodiq (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2024)
This study aims to explore the concept of "defending the truth" and its relevance to contemporary Muslim life, based on Surah Al-‘Asr and other Qur’anic and Prophetic texts. The research uses an analytical-descriptive approach through literature review of Qur’anic verses, Hadiths, and scholarly interpretations. The findings reveal that defending the truth encompasses more than speaking out; it includes righteous actions, da’wah, striving in God’s cause, offering sincere advice, and enjoining good and forbidding evil, with wisdom and compassion. The study emphasizes that patience is an essential companion to defending the truth due to the inevitable trials and resistance faced. Surah Al-‘Asr outlines four essential principles, faith, righteous deeds, mutual enjoining of truth, and patience, which serve as a complete guide for personal and communal reform. The research concludes that every Muslim is obligated to uphold the truth in accordance with Islamic principles, contributing to the moral integrity and strength of the ummah.